Answer:
Here,
Angle TUV + Angle NUV=TUV
By substituting the provided or given value ls in the question we obtain,
1+38x+66 Degree= 105x
1+66 Degree= 67x
67 Degree= 67x
1 Degree = x
x = 1 Degree
Therefore
Angle TUN=1+38x=39
Angle NUV=66 Degree
Therefore
1+38x+66 Degree= 105x
=39 Degree+66 Degree= 105 Degree
Therefore
Angle TUV=105 Degree
Answer:she dosnt have enough
Step-by-step explanation:bored
Answer:
Option D
Step-by-step explanation:
In this question we use properties of parallelogram and angle sum property of a triangle.
In parallelogram ABCD
![\angle ABC=40^\circ](https://tex.z-dn.net/?f=%20%5Cangle%20ABC%3D40%5E%5Ccirc%20)
As, we know that opposite angles of parallelogram are equal
Therefore,
![\angle ABC =\angle ADC =40^\circ](https://tex.z-dn.net/?f=%20%5Cangle%20ABC%20%3D%5Cangle%20ADC%20%3D40%5E%5Ccirc%20)
Now, in triangle ADC
We know that sum of all the angles of a triangle is ![=180^\circ](https://tex.z-dn.net/?f=%3D180%5E%5Ccirc)
![\angle ACD +\angle ADC +\angle DAC =180^\circ](https://tex.z-dn.net/?f=%5Cangle%20ACD%20%2B%5Cangle%20ADC%20%2B%5Cangle%20DAC%20%3D180%5E%5Ccirc)
![57^\circ +40^\circ +\angle DAC =180^\circ](https://tex.z-dn.net/?f=57%5E%5Ccirc%20%2B40%5E%5Ccirc%20%2B%5Cangle%20DAC%20%3D180%5E%5Ccirc)
![97^\circ + \angle DAC = 180^\circ](https://tex.z-dn.net/?f=97%5E%5Ccirc%20%2B%20%5Cangle%20DAC%20%3D%20180%5E%5Ccirc%20)
Subtracting 97 from both sides we get
![\angle DAC = 180^\circ - 97^\circ](https://tex.z-dn.net/?f=%20%5Cangle%20DAC%20%3D%20180%5E%5Ccirc%20-%2097%5E%5Ccirc%20)
![\angle DAC = 83^\circ](https://tex.z-dn.net/?f=%20%5Cangle%20DAC%20%3D%2083%5E%5Ccirc%20)
Measure of ![\angle CAD = 83^\circ](https://tex.z-dn.net/?f=%5Cangle%20CAD%20%3D%2083%5E%5Ccirc%20)
Question 3:
If the diver is being pulled up at 25 feet every minute, in 10 minutes they would have been pulled up 10 times that
10*25=250
The diver is now 200 feet below, but 10 minutes ago they would have been 250 feet deeper so:
200+250=450
450 feet
To complete the solution of - x - 8y = -1, we first need to substitute x for -15.
As so:
-(-15) - 8y = -1
15 - 8y = -1
Next, we can subtract 15 from each side to get:
15 - 15 - 8y = -1 - 15
- 8y = -16
Now, we can divide by -8 on each side to get the y by itself:
-8y / -8 = -16 / -8
y = -16 / -8
y = 2
There we go! <em>y</em> = 2 when x = -15! Hope I could help you out! Have a good one.